PERAN KADER LANSIA DALAM MENINGKATKAN DERAJAT KESEHATAN LANSIA - Budi Punjastuti; Pritta Yunitasari; Siti Maryati (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2020)
ABSTRACT Background: Indonesia is currently in an aging population structure because the population aged 60 years and over (elderly) has exceeded 7%, reaching 9.03% or as many as 23.66 million people. Where DI Yogyakarta Province ranks first with the highest number of elderly in Indonesia, amounting to 13.81% (Ministry of Health Republic of Indonesia in 2017). Basic Health Research in 2013, showed that most diseases in the elderly were hypertension (57.6%), the rest were arthritis, stroke and several other diseases. From the description, the elderly's health care should prioritize promotion and prevention with the support of quality curative and rehabilitative services in health facilities. In a preliminary survey on RW 05 Pakuncen Wirobrajan DIY on March 30, 2019, an examination was carried out on the residents of the area where the elderly who did the examination about 70% of those who did the examination found that the elderly who suffer from hypertension 44 people, the results of the examination of blood sugar levels 28 people, increased uric acid 21 people and increased cholesterol 12 people. The elderly are asking about why there has been an increase in the results of examinations and how to manage them so that the elderly remain healthy. The cadre of the elderly cadre also wants to monitor health as early as possible to the elderly before the elderly is brought to the puskesmas. Objective: So that the elderly can behave in a healthy life and the community, especially the elderly cadres, are able to monitor and check as early as possible for the elderly with health problems Methods: Cadre training, health counseling, periodic examination of the elderly and evaluation of cadre activities during managing the elderly. Results: The elderly cadre was able to manage the elderly at least 2 elderly, the elderly cadre was able to measure blood pressure, the activity of ROM exercises and cognitive therapy in the elderly who have problems with their health, the elderly exercise periodically. Health education about Hypertension and Diabelitus mellitus was carried out by the community service team with the results of monitoring a decrease in blood pressure measurement results and a decrease in blood sugar levels during the examination 1. Blood pressure above normal limits: 16 elderly (24.24%), Blood pressure in the Normal limit: 50 elderly (75, 76%), Blood sugar levels when above the normal limit: 8 elderly (12.12%), Blood sugar levels when within the normal limit: 58 elderly (87, 88%) Second blood test above the normal limit : 11 elderly (19.64%), blood pressure within normal limits: 45 elderly (80.36%), blood sugar levels when above the normal limit: 11 elderly (19.64%), blood sugar levels when within normal limits: 45 elderly (80, 36%) Conclusion: Elderly cadres are able to carry out independent and regular checks on the elderly Keywords: elderly cadres